A CENTURY OF UNEVEN AND COMBINED DEVELOPMENT: THE EROSION OF UNITED STATES HEGEMONY AND THE RISE OF CHINA - Michael Dunford; Liu Weidong (Vestnik MGIMO-Universiteta)
The concept of uneven and combined development where the interconnectedness and interactions of different societies shape and combine with their internal structures to drive the evolution of comparative development and power is used to examine the drivers of successive phase of global development in the 100 years since 1917. This concept was coined by left-wing theorist and the Soviet Communist party leader Leo Trotsky with the aim of explaining peculiarities of imperialRussia’s development. Currently it is applied for different cases of political and economic development on the global level. The concept of uneven and combined development allows taking into account both intra-state and extra-state factors, including political regimes evolution, international trade dynamics.   Most attention is paid to the drivers of secular economic decline in the United States and the Western world, the way it was tempered by a wave of productive and financial globalization that itself permitted the rise of a number of emerging economies with the economic, political and cultural capacity to exploit latecomer advantage and the way the rise of new powers is leading in the direction of a polycentric multi-civilizational world and a possibly more inclusive model of development. To put it simply, the article addresses political economy of global power shifts and their prospects.